Message in a bottle: process innovations in the cork stopper industry - Sarkar, Soumodip (2012)
The simple cork provides a fascinating illustration of an industry that has survived and dominated for over five centuries as the only stopper of choice. This dominance is now however under serious threat from alterative stoppers namely synthetic and aluminium screw caps. This paper analyzes how the cork stopper industry is attempting to resolve the problems of technical efficiency arising from the contamination by TCA and other volatiles. We use the case of Amorim and Irmãos S.A., the single largest cork stopper manufacturer in the world with over one-fourth of the global market share, analyzing it’s process innovations in the battle against contamination. The success of these process innovations could well prove crucial for the entire cork industry not only to stem the rise of alternative stoppers but also in recapturing some of the lost market share.